Wing vein abnormality analysis in honeybee (Apis mellifera L. 1758) populations from Iran - Mahdi Shahshahani; Roohollah Abbasi (Scientific Reports, 2024)
Abstract The insect wing is one of the most important characteristics that allowed insects to occupy most of the habitats on the planet. Honeybee wings has been the subject of studies on the venation abnormalities. A total of 424 honeybees from 14 locations were collected and all four wings were removed and examined for 19 abnormalities on the forewings and 6 abnormalities on the hindwings. In general, supernumerary veins were the most common abnormalities seen and abnormalities no. 23, 2, 6, 1, 5, 21, 10, 13 had the highest and abnormalities no. 11, 17, 18, 19, 20, and 25 had the lowest frequencies. All of the abnormalities had similar frequencies in the right and left wings in the population. In terms of correlation between 25 abnormalities, abnormality pairs AB3–AB13, AB6–AB7, AB7–AB8, AB10–AB12, AB16–AB17 on the forewing and AB2–AB23, AB12–AB20, AB12–AB24, AB13–AB21, AB16–AB25, and AB17–AB25 between the forewing and hindwing show significant positive correlations and abnormality pairs AB4–AB5, AB7–AB15 and AB8–AB9 on the forewing show significant negative correlations with each other. In terms of the differential occurrence of abnormalities , a few locations differed significantly from other locations. This study provides some insights into the nature of these abnormalities on the honeybee wings.